Student Comprehension of The Concept of a Geometrical Figure: The Case of Straight Lines and Parallel Line - Patrick Tchonang Youkap (JME (Journal of Mathematics Education), 2021)
The objective of this paper is to identify some student’s conceptions of the straight line and two parallel lines. This will allow us to evaluate the distance that exists between their conceptions and the theory of these concepts. In doing so, we analyzed the students’ answers to a questionnaire: the questionnaire concerned the explication of the straight line and two parallel lines. The results indicate that the students have difficulties to produce an acceptable definition of a straight line and two parallel lines. They have difficulties to find appropriate terms to express their comprehension of these concepts. The definitions they produce are ambiguous and seem to be related to the drawings they have encountered in the classroom. Their answers indicate that their comprehension on the straight line and two parallel lines seem to be in conflict with the theory of these concepts.